A SYSTEMATIC APPROACH TO THE FORMATION OF VISUAL AND INFORMATION CULTURE PRE-SERVICE MATHEMATICS AND COMPUTER SCIENCE TEACHERS - Drushlyak, M.; Shamonia, V. (Physical and Mathematical Education, 2021)
Formulation of the problem. Today there is a change in the way young people perceive information, which leads to the demand for highly qualified professionals, including teachers, with a high level of formation of visual and information culture. However, the formation of visual and information culture of pre-service mathematics and computer science teachers should not be fragmentary, "from case to case", but within the pedagogical system, based on a systematic approach as a leading methodological approach.Materials and methods. The study was based on findings of national and foreign scientists who study the training of pre-service mathematics and computer science teachers, as well as explore the conceptual foundations and principles of a systematic approach to training. To achieve this goal, the methods of the theoretical level of scientific knowledge were used: analysis of scientific literature, synthesis, formalization of scientific sources, description, and comparison.Results. From the standpoint of a systematic approach, the pedagogical system of formation of visual and information culture of pre-service mathematics and computer science teachers was considered as an open (interacts with other systems), dynamic (its content and organizational and technological content is constantly improving) system, which is implemented in the unity of general (formation of visual and information culture is part of the professional training of pre-service mathematics and computer science teachers), special (specific features of mathematical education, computer education, the availability of specialized software), individual (individual characteristics of students and educational features). process of a particular institution of higher education). In the context of the study, a systematic approach allows us to consider the process of formation of visual and information culture of pre-service mathematics and computer science teachers as a complex holistic dynamic process that focuses on achieving a specific goal and provides systematic scientific and methodological support of individual computer science and mathematics courses, purposeful improvement of the system of continuous postgraduate education of pedagogical workers and topics of qualification works.Conclusions. The following provisions provide effective formation of visual and information culture of pre-service mathematics and computer science teachers. The first one: the process of formation of visual and information culture of pre-service mathematics and computer science teachers is based on a systematic approach and balanced combination of computer-mathematical, pedagogical and informational training. The second: updating the content of professional training of pre-service mathematics and computer science teachers is by developing scientific and methodological support for individual computer science and mathematics courses and special courses. The third: creating conditions for the implementation of individual educational trajectories, rational and balanced use of specialized software, visualized tasks, and purposeful formation of skills to critically evaluate and rationally choose computer tools. The forth: the use of common and innovative forms, methods and teaching aids for a balanced relationship between theory and practice in educational and professional activities in order to develop skills and abilities to work with visualized educational material.
Keywords: system; pedagogical system; system approach; visual and information culture; pre-service mathematics and computer science teachers